The Properties of Wool-based Activated Carbon Tubes Prepared by Potassii with no Gas and Its Mechanism Stud (Journal of Fiber Bioengineering and Informatics, 2019)
In this study, the wool-based activated carbon tubes (ACTs) were successfully prepared by potassiias additive. The ACTs had formed a tubular morphology with numerous pores located in both twosides. The mechanism of the tube formation were mainly investigated by removing overlapping scaleson the surface of fibers and comparing the effects of experimental parameters. The removal methodwere carried out by formic acid and ultrasonic wave oscillation. The influence between scales and tubeswas characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA), methyleneblue (MB) through discussing the morphology study, thermal property and adsorption capacity of ACTs.The surface morphology of the ACTs were affected by carbonization temperature, while the scale layershas no relations with the formation of a tubular morphology. Scale layers had almost no effects onthermal decomposition because close weight loss between ACKC2 and ACKC5. The adsorption capacityof ACTs from raw wool using two-step method is in the range of 18.50-26.75 mg/g, which was obviouslyhigher than using one-step method with 14.40-84.00 mg/g. The adsorption capacity of ACTs decreasedbecause of the removal of scale layers using one-step, which is contrary to ones using two-step.